ANALYSIS OF CITRUS FRUIT SUPPLY CHAIN MANAGEMENT PERFORMANCE EFFICIENCY IN SIMALUNGUN REGENCY - Prindo Pranata Tarigan; Nazaruddin; Iskandarini (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The research aims to analyze the efficiency of supply chain management in determining the price of oranges in Simalungun Regency. The current study employs a causal effect research design. The sample consists of 126 orange farmers in Dolok Silou District, Simalungun Regency. The research utilizes Analytic Hierarchy Process (AHP) and Supply Chain Operations Reference (SCOR) analysis techniques. Findings indicate that the supply chain management of oranges in Simalungun Regency demonstrates high efficiency, particularly in planning, market demand responsiveness, production processes, and distribution. Alternative 3 consistently shows the highest performance across all matrices in AHP, reflecting excellence in these aspects. The SCOR results yield a final score of 0.2983, emphasizing the significance of planning (40%) and production (25%) in achieving overall supply chain efficiency. Responsiveness to market demand, effective planning strategies, and optimal production processes are crucial in determining efficient pricing, laying the groundwork for competitive advantages through operational efficiency and adaptation to local market dynamics.